Personal Branding Young Activist Pada Akun Instagram Melati Wijsen - Dana Devi, Putu Jista Prajna; Sugiarica Joni, I Dewa Ayu; Pradipta, Ade Devia (E-Jurnal Medium, 2021)
Personal branding is how an individual represent their skills, ideas, and belief. A brand for public figure like young activist is important to be formed in order to gain sympathy and acceptance from the society. In this research, reasearcher wants to describe how young activist, Melati Wijsen formed and applied personal branding through social media instagram. This research used qualitative descriptive approach and analyzed using Peter F. Montoya’s Eight Laws Of Personal Branding. The result of this research shows that young activist, Melati Wijsen has a brand as an activist who is inspiring, consistent, hard working and humble. Melati Wijsen has successfully implemented Eight Laws Of Personal Branding in forming her brand, with The Law Of Leadership, The Law Of Personality, and The Law Of Visibility being the most stand out concept in forming her personal brand through social media instagram. Keyword : Personal Branding, Young Activist, Eight Laws Of Personal Branding, Instagram